148k views
5 votes
Solve for x in the equation x² - 4x - 9 = 29.

Solve for x in the equation x² - 4x - 9 = 29.-example-1
User Nardecky
by
5.8k points

2 Answers

3 votes

Answer:

Choice a is correct answer.

Explanation:

Given equation is :

x²-4x-9 = 29

Adding -29 to both sides of above equation , we get

x²-4x-9-29 = -29+29

x²-4x-38 = 0

ax²+bx+c = 0 is general quadratic equation .

Comparing given equation with quadratic equation , we get

a = 1 , b = -4 and c = -38

x = (-b±√b²-4ac) / 2a

Putting above values in quadratic equation, we get

x = ( -(-4) ± √(-4)²-4(1)(-38) ) / 2(1)

x = ( 4±√16+152) / 2

x = ( 4± √168) / 2

x = (4±√4×42) / 2

x = (4±2√42) / 2

taking 2 common, we get

x = 2( 2±√42) / 2

x = 2±√42 which is the answer.



User Svenwltr
by
6.3k points
4 votes

Answer: First option.


Explanation:

1. To solve this problem you can applly the quadratic formula, which is shown below:


x=\frac{-b+/-\sqrt{b^(2)-4ac}}{2a}

2. The quadratic equation is:


x^(2)-4x-9-29=0\\x^(2)-4x-38=0

3. Then:

a=1

b=-4

c=-38

4. Therefore, when you substitute these values into the quadratic formula, you obtain the following result:


x=\frac{-(-4)+/-\sqrt{(-4)^(2)-4(1)(-38)}}{2(1)}

x=2±√42


User Carson Evans
by
5.8k points